The Use of Code Switching by English Lecturers of English Department - Sarita Merilia; Ismi Adinda (Universitas Pamulang, 2020)
This research aims at investigating types of code switching used by lecturers and what are the reasons among English lecturers in English Department of Universitas Pamulang. Out of 70 lecturers of the population, 33 lecturers were chosen as the samples based on the random sampling. The data in this study were obtained through questionnaires (open-ended questionnaire). This study revealed that tag switching is a type of code switching which is mostly used by the English lecturers. Then Intra sentential is the second type which is used by the lecturers and the last is inter sentential. Lecturers identified a number of reasons of using code switching in classrooms: teaching new students, making students to understand the material conveyed, avoid the miss understanding toward the material, no appropriate word, creating effective communication and other problems